KINERJA FINANSIAL DAN OPERASIONAL BADAN USAHA MILIK NEGARA YANG GO PUBLIC - Tona Aurora Lubis (Jurnal Keuangan dan Perbankan, 2011)
The main purpose of this study was to find out the effects of public ownership as the result of privatization byinitial public offering (IPO) on financial and operational performance in private state owned enterprises(SOE). Target populations of this research were 9 private SOEs. The analysis of the study used partial leastsquare (PLS). The finding of this study showed that public ownership, as the result of privatization, mightimprove financial and operational performance only at leverage decrease and profitability increase.